A health economic guide to market access of biosimilars. (2nd January 2021) - Simoens, Steven; Vulto, Arnold G.
ABSTRACT: Introduction : Little is known about market access to biosimilars from a health economic perspective, except for studies that compute the budget impact of biosimilar use. Areas covered : This comprehensive health economic guide to the market access of biosimilars focuses on the role of biosimilars in pharmaceutical innovation and competition, the objective of biopharmaceutical policy, the budget impact of biosimilars, and the cost-effectiveness of biologic therapy in the presence of biosimilars. Expert opinion : We argue that the objective of biopharmaceutical policy in a health system should be to create a competitive and sustainable market for off-patent reference biologics, biosimilars, and next-generation biologics that makes biologic therapy available to patients at the lowest cost. Market access of biosimilars can contribute to this objective as a result of the lower price of biosimilars and price competition with alternative therapies. The resulting improvement in the cost-effectiveness of biologic therapy needs to be accounted for by revisiting reimbursement decisions and conditions. When examining the cost-effectiveness of biologic therapy following patent expiry, stakeholders need to consider residual uncertainties at the time of biosimilar marketing authorization, the nocebo effect, market entry of a second-generation reference biologic with a different administration form than the biosimilar, and value-added services.